Oleamide-Mediated Polarization of M1 Macrophages and IL-1β Production by Regulating NLRP3-Inflammasome Activation in Primary Human Monocyte-Derived Macrophages - Wisitpongpun, Prapakorn; Potup, Pachuen; Usuwanthim, Kanchana (Frontiers in Immunology, 2022)
Macrophages are a type of innate immune cell that activates the NLRP3 inflammasome, causing the release of the cytokine IL-1, which is a crucial mediator of the inflammatory response. NLRP3 activation that is dysregulated worsens a variety of inflammatory and autoimmune diseases, as well as neurodegenerative diseases. Oleamide is an endogenous fatty acid amide that was first determined as a sleep-inducing molecule and later shown to have wide-ranging beneficial effects on the central nervous system. How oleamide influences human macrophage polarization and NLRP3-inflammasome activation remains unclear. The effect of oleamide on macrophage polarization was explored using an in vitro culture of primary human monocyte-derived macrophages (MDMs) supplemented with human serum-containing media. Cellular and molecular mechanisms of oleamide-regulated MDMs polarization were also investigated. Results showed that oleamide promoted naïve macrophages (M0) toward the M1 phenotype by upregulating M1-associated genes (IL-1β, iNOS, CXCL10), along with downregulation of M2-associated genes (Arg-1, CD206, CCL22). Cell surface expression indicated that oleamide enhanced CD80 expression in M0 naïve macrophages and hider CD206 and CD163 expression in M2 macrophages. Higher production of IL-1β cytokine was observed but with no alteration in IL-6 and TNF-α levels by MDMs and differentiated THP-1 models. Whether oleamide functioned as a second signal that activated the NLRP3 inflammasome and mediated IL-1β production was further investigated using LPS-primed MDMs followed by oleamide treatment that induced activation of inflammasome-related proteins including NLRP3, ASC, cleaved casp-1, and cleaved IL-1β. These findings suggested that oleamide promoted M1 macrophage polarization and increased IL-1β production by activating the NLRP3 inflammasome in primary MDMs. This research reveals a new function for oleamide as well as prospective targets for treating NLRP3-related inflammatory disorders.